Analysis of Social Challenges in the Context of Bhakti Era Poetry: भक्तिकालीन काव्य के संदर्भ में सामाजिक चुनौतियों का विश्लेषण - Bisoriya, Harisingh; Goyal, Mamta (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Literature serves as a mirror of its time and is integral to the fabric of society, with both being deeply interconnected. Social activities and expressions significantly reinforce the foundation of literature while ensuring its contemporary relevance. The tradition of Bhakti poetry has flowed from the medieval Bhakti movement, but the absence of true knowledge often weakened the emotional fervor of devotion. In Bhakti, the strength of means and ends plays a pivotal role in shaping a robust spiritual path. Social life, when guided by ideals, often clashes with the values of rigid traditions and customs. This conflict leads to the evolution of social realities, reflected creatively and intellectually in literature. Over time, these reflections have become deeply rooted in contemplation and interconnected with societal actions, manifesting as authentic expressions of contemporary realities. Abstract in Hindi Language: साहित्य अपने समय का दर्पण है साहित्य के बिना समाज की कल्पना नहीं की जा सकती समाज और साहित्य एक दूसरे से जुड़े है सामाजिक गतिविधिया, स्वर साहित्य की बुनियाद को सशक्त बनाती हुई समसामयिक प्रासंगिक भी। भक्तिकाव्य की परम्परा परवर्ती काल से प्रवाहमान रही है, किन्तु भक्ति, ज्ञान के अभाव के कारण भावना का उन्मेष कमजोर रहा साधन और साध्य की प्रबलता भक्ति के मार्ग में सशक्त पक्ष रखती है। सामाजिक जीवन आदर्शो के लीक पर ले चलने की वजह से रूढ़ियों और परम्पराओं के मूल्यों से परस्पर टकराती रही, जिसके कारण सामाजिक स्थितियां चिंतनशील होकर सृजनात्मक रूप से साहित्य में परिवर्तित होने लगी जिसका मूल चिंतनमूलक होकर सामाजिक क्रियाओं से जुड़कर यथार्थ रूप में परिलक्षित हो उठी। Keywords: धर्म-साधना, भक्तिकाल, विविध धर्मो, भारतीय समाज।